In Situ Investigation of Deformation Mechanisms and Stress Evolution in Mg-3Al-1Zn (AZ31) Alloy Using Synchrotron X-Ray Microdiffraction - Yuxin Cao; Li Li; Yong Wang; Tuo Ye; Changping Tang (Metals)
This study employs synchrotron polychromatic X-ray microdiffraction (micro-XRD) to resolve the dynamic interplay between deformation mechanisms and stress redistribution in a commercial Mg-3Al-1Zn (AZ31) alloy under uniaxial tension. Submicron-resolution mapping across 13 incremental load steps (12–73 MPa) reveals sequential activation of deformation modes: basal slip initiates at 46 MPa, followed by tensile twinning at 64 MPa, and non-basal slip accommodation during twin propagation at 68 MPa. Key findings include accelerated parent grain rotation (up to 0.275° basal plane tilt) between 43–46 MPa, stress relaxation in parent grains coinciding with twin nucleation, and a ~35 MPa stress reversal within twins. The critical resolved shear stress (CRSS) ratio of twinning to basal slip is experimentally determined as 1.8, with orientation-dependent variations attributed to parent grain crystallography. These results provide unprecedented insights into microscale deformation pathways, critical for optimizing magnesium alloy formability and performance in lightweight applications.